2015
DOI: 10.1159/000368118
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Analysis of Electroencephalographic Changes during Photic Driving Responses in Patients with Migraine

Abstract: Objective: Migraineurs demonstrate abnormal information processing such as photic hypersensitivity. The photic driving response to photic stimulation (PS) is a reaction to the visual stimulation of electroencephalography (EEG). Both the photic driving response and photic hypersensitivity appear during light stimulation. We considered that evaluation of a migraineur's photic driving response may help to elucidate the mechanism of the migraineur's sensitive condition. Our study aimed to investigate EEG photic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Photic driving by photic stimulation of high frequency (≥15 Hz) is called the H-response, and is observed in the interictal phase in migraine patients [4]. We have observed the photic driving response at a flashing rate of > 15 Hz in migraine patients, and there was a tendency towards more frequent photic driving response in migraine patients with photic hypersensitivity, regardless of the aura status [5]. Additionally, the findings of an anterior shift of the activated area during photic stimulation, which was more marked in patients with longer disease duration, and a positive correlation between GFP values and disease duration [5] suggest central sensitization of the limbic system in migraine patients [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photic driving by photic stimulation of high frequency (≥15 Hz) is called the H-response, and is observed in the interictal phase in migraine patients [4]. We have observed the photic driving response at a flashing rate of > 15 Hz in migraine patients, and there was a tendency towards more frequent photic driving response in migraine patients with photic hypersensitivity, regardless of the aura status [5]. Additionally, the findings of an anterior shift of the activated area during photic stimulation, which was more marked in patients with longer disease duration, and a positive correlation between GFP values and disease duration [5] suggest central sensitization of the limbic system in migraine patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…We have observed the photic driving response at a flashing rate of > 15 Hz in migraine patients, and there was a tendency towards more frequent photic driving response in migraine patients with photic hypersensitivity, regardless of the aura status [5]. Additionally, the findings of an anterior shift of the activated area during photic stimulation, which was more marked in patients with longer disease duration, and a positive correlation between GFP values and disease duration [5] suggest central sensitization of the limbic system in migraine patients [14]. In the present study using eLORETA, we observed significant differences in responses to photic stimulations at frequencies 5, 8, 15, and 20 Hz between MWA and MWOA groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In fact, these patients demonstrate abnormal information processing such as photic hypersensitivity. 26 In fact, these patients demonstrate abnormal information processing such as photic hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…26 Both the photic driving response and photic hypersensitivity appear during light stimulation and were increased in migraineurs. 26 Also, migraine is linked with various comorbid conditions, the most prominent being motion sickness. 26 Also, migraine is linked with various comorbid conditions, the most prominent being motion sickness.…”
Section: Discussionmentioning
confidence: 99%